2008
DOI: 10.1016/j.camwa.2007.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Almost periodic solutions of neutral functional differential equations

Abstract: In this paper we study a non-autonomous neutral functional differential equation in a Banach space. Applying the theory of semigroups of operators to evolution equations and Krasnoselskii's fixed point theorem we establish the existence and uniqueness of a mild almost periodic solution of the problem under consideration.The theory of almost periodic functions was first treated and created by Bohr during 1924Bohr during -1926. Later on Bochner extended the Bohr theory to general abstract spaces. The theory has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…The authors have shown the existence of an almost periodic solution of a neutral functional differential equation using the Krasnoselskiis fixed point theorem and the theory of semigroups in their previous work [1]. A similar result has also been established by the authors [2] using the theory of monotone operators.…”
Section: Introductionmentioning
confidence: 74%
“…The authors have shown the existence of an almost periodic solution of a neutral functional differential equation using the Krasnoselskiis fixed point theorem and the theory of semigroups in their previous work [1]. A similar result has also been established by the authors [2] using the theory of monotone operators.…”
Section: Introductionmentioning
confidence: 74%
“…They were introduced by Bochner [1,2]; for more details about this topic, we refer the reader to [3,4]. In recent years, the existence of almost periodic and almost automorphic solutions on different kinds of deterministic differential equations have been considerably investigated in lots of publications [5][6][7][8][9][10][11][12][13][14][15] because of its significance and applications in physics, mechanics, and mathematical biology.…”
Section: D[x(t) − F T B 1 X(t) ] = [Ax(t) + G(t B 2 X(t))]dt + H(tmentioning
confidence: 99%
“…For example, these equations arise in the study of two or more simple oscillatory systems with some interconnections between them [1,2], and in modeling physical problems such as vibration of masses attached to an elastic bar [2]. Qualitative analysis such as periodicity, almost periodicity and stability of functional equations have been studied by many researchers (see [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]20] and the references cited therein). More recently researchers have given special attention to the study of neutral differential equations, see [3,4,8,18,12,13,15,16] and references cited therein.…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative analysis such as periodicity, almost periodicity and stability of functional equations have been studied by many researchers (see [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]20] and the references cited therein). More recently researchers have given special attention to the study of neutral differential equations, see [3,4,8,18,12,13,15,16] and references cited therein. Recently, Islam and Raffoul [12] have studied the periodic solution of a nonlinear neutral system of the form dx(t) dt = A(t)x(t) + d dt Q (t, x(t − g(t))) + G(t, x(t), x(t − g(t))), (1.1) where A(t) is a nonsingular n × n matrix with continuous-real-valued functions as its elements.…”
Section: Introductionmentioning
confidence: 99%